(untitled) (Research, Society and Development, 2025)
Gingival Recession (GR) is characterized by the loss of gingival tissue around the teeth, which can compromise aesthetics, favor dentin hypersensitivity, increase the risk of root caries, and hinder biofilm control. It is a common finding in daily clinical practice. Objective: to verify, through a narrative review, the current evidence related to the risk factors, etiology, and treatment of GR. Methodology: cross-sectional studies, longitudinal studies, and systematic reviews indexed in the MEDLINE and PubMed databases, in Portuguese or English, were selected using the terms “gingival recession and etiology,” “gingival recession and epidemiology,” and “gingival recession and surgery,” or simply “gingival recession.” Discussion: Epidemiological surveys and longitudinal studies report that GR is highly prevalent in the adult population, with more than 50% of individuals presenting one or more sites with gingival recession of 1 mm or more. Its etiology is multifactorial, with different related factors that may act in association, such as bacterial biofilm, traumatic toothbrushing, local plaque-retentive factors, smoking, and orthodontic movement. Connective tissue grafting remains the most predictable clinical approach for root coverage in GR. Conclusion: The mechanism by which GR occurs is still not well understood. It is a common condition reported in most populations, frequently perceived by patients, leading them to seek professional guidance and treatment.